Primary age‐related tauopathy in a Finnish population‐based study of the oldest old (Vantaa 85+). (23rd January 2022) - Savola, Sara; Kaivola, Karri; Raunio, Anna; Kero, Mia; Mäkelä, Mira; Pärn, Kalle; Palta, Priit; Tanskanen, Maarit; Tuimala, Jarno; Polvikoski, Tuomo; Tienari, Pentti J.; Paetau, Anders; et al.
Abstract: Aims: Few studies have investigated primary age‐related tauopathy (PART) in a population‐based setting. Here, we assessed its prevalence, genetic background, comorbidities and features of cognitive decline in an unselected elderly population. Methods: The population‐based Vantaa 85+ study includes all 601 inhabitants of Vantaa aged ≥ 85 years in 1991. Neuropathological assessment was possible in 301. Dementia (DSM IIIR criteria) and Mini‐Mental State Examination (MMSE) scores were assessed at the baseline of the study and follow‐ups. PART subjects were identified according to the criteria by Crary et al and were compared with subjects with mild and severe Alzheimer's disease (AD) neuropathological changes. The effects of other neuropathologies were taken into account using multivariate and sensitivity assays. Genetic analyses included APOE genotypes and 29 polymorphisms of the MAPT 3′ untranslated region (3 ′ UTR region). Results: The frequency of PART was 20% ( n = 61/301, definite PART 5%). When PART subjects were compared with those with severe AD pathology, dementia was less common, its age at onset was higher and duration shorter. No such differences were seen when compared with those with milder AD pathology. However, both AD groups showed a steeper decline in MMSE scores in follow‐ups compared with PART. APOE ε4 frequency was lower, and APOE ε2 frequency higher in the PART group compared with each AD group. The detected nominally significant associations between PART and two MAPT 3 ′ UTR polymorphisms and haplotypes did not survive Bonferroni correction. Conclusions: PART is common among very elderly. PART subjects differ from individuals with AD‐type changes in the pattern of cognitive decline, associated genetic and neuropathological features. Abstract : Few studies have investigated primary age‐related tauopathy (PART) in a population‐based setting. Here we assessed its prevalence, genetic background, comorbidities, and features of cognitive decline in an unselected elderly population. We found that PART is common among very elderly and differs from Alzheimer's disease in terms of neuropathological features, pattern of cognitive decline, and associated genetic factors and comorbidity pathologies. Thus, it is important to distinguish PART and other novel neuropathological entities from the classical neuropathological diseases.